2021
DOI: 10.3389/fimmu.2021.677550
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin/AdipoR1 Axis Promotes IL-10 Release by Human Regulatory T Cells

Abstract: BackgroundAdiponectin is an important immunomodulatory mediator in inflammatory conditions. While we previously showed that adiponectin receptor 1 (AdipoR1) is expressed in murine regulatory T cells (Tregs), its expression in human Tregs remain unknown. Here, we examined the expression of AdipoR1 in human Tregs and whether its ligand, globular adiponectin (gAd) affects the Treg ability to secrete IL-10 and the role of Type 2 (T2) inflammation in such process.MethodsHuman Tregs from peripheral blood were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…In contrast, adiponectin stimulates insulin function [ 12 , 58 , 59 ] and sensitivity [ 59 ], and its levels are negatively correlated with waist circumference, visceral fat weight, triglycerides and HDL levels, fast glucose and insulin levels, and also with the development of type 2 diabetes [ 78 80 ]. Interestingly, leptin and adiponectin play opposite roles to Treg balance: while leptin inhibits Treg function [ 81 , 82 ], adiponectin promotes regulatory functions, including IL10 production [ 83 ]. IL10 possess various cellular sources, being Tregs a major producer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, adiponectin stimulates insulin function [ 12 , 58 , 59 ] and sensitivity [ 59 ], and its levels are negatively correlated with waist circumference, visceral fat weight, triglycerides and HDL levels, fast glucose and insulin levels, and also with the development of type 2 diabetes [ 78 80 ]. Interestingly, leptin and adiponectin play opposite roles to Treg balance: while leptin inhibits Treg function [ 81 , 82 ], adiponectin promotes regulatory functions, including IL10 production [ 83 ]. IL10 possess various cellular sources, being Tregs a major producer.…”
Section: Discussionmentioning
confidence: 99%
“…These effects were not reproduced in another study which showed that the effects of ADPN depend on the polarization of the cell; in M1 macrophages, ADPN triggers the expression of proinflammatory cytokines (IL-6, TNFα, IL-12), whereas in M2 macrophages it induces the expression of IL-10 [35,36] and IL-1 receptor antagonist [37]. IL-10 secretion is further enhanced by ADPN's effects on regulatory T lymphocytes (Tregs) [38].…”
Section: Main Roles Of Adpnmentioning
confidence: 98%
“…Peripheral Tregs express more AdipoR1 than thymus-derived ones. Globular ADPN increases the secretion of IL-10 in peripheral Tregs, particularly in a Th2 milieu [38], in macrophages, monocytes and dendritic cells [37]. In macrophages, IL-10 induces the mRNA expression of the tissue inhibitor of metalloproteinase 1 (TIMP-1) [36].…”
Section: Inflammation and Immune Responsementioning
confidence: 99%
“…Considering this evidence, recent in vivo and in vitro studies have explored the relationship between levels of these adipokines and lung diseases, revealing that leptin and adiponectin can directly regulate lung inflammation and immune function [69,[94][95][96][97]. As a matter of fact, it has been observed that adipoR1 is expressed in immune regulatory T cells (Tregs) in the lungs and modulates the immune response during pulmonary inflammation [69].…”
Section: Leptin Adiponectin and Pulmonary Dysfunctionmentioning
confidence: 99%
“…Therefore, the balance between these two cell populations is essential for the regulation of the immune system. In vivo studies on mice showed that activation of adipoR1 in lung Tregs promoted their proliferation and activity, thereby suppressing the immune response and inflammation [95]. However, this mechanism was impaired in obesity due to downregulation of adipoR1 expression, reducing Treg activity and promoting airway inflammation [69].…”
Section: Leptin Adiponectin and Pulmonary Dysfunctionmentioning
confidence: 99%